1996
DOI: 10.1007/bf02523373
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical carbon dioxide extraction of fatty and waxy material from rice bran

Abstract: Waxy and fatty materials were removed from rice bran by supercritical carbon dioxide at pressures up to 28 MPa and temperatures between 40 and 70°C. The yields of the supercritical extraction were only 16–60% of those obtained by Soxhlet extraction with hexane. The highest yield was reached at the highest pressure and temperature used (28 MPa and 70°C), indicating that supercritical extraction of this lipid‐bearing material could probably be improved at more severe extraction conditions. The supercritical extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…Most studies for the use of SC-CO 2 in lipid extraction have focused on the yield of extractable material. However, each compound possesses a unique extractability under different conditions of supercritical fluid extraction 29 . In addition, current publications indicated high phytochemicals including oryzanol in colored rice especially black rice, similar to HN in this study 30 32 .…”
Section: γ-Oryzanolmentioning
confidence: 99%
“…Most studies for the use of SC-CO 2 in lipid extraction have focused on the yield of extractable material. However, each compound possesses a unique extractability under different conditions of supercritical fluid extraction 29 . In addition, current publications indicated high phytochemicals including oryzanol in colored rice especially black rice, similar to HN in this study 30 32 .…”
Section: γ-Oryzanolmentioning
confidence: 99%
“…Garcia et al (1996) reported that most studies of the use of SFE in lipid extraction have focused on the yield of extractable material. In theory, each compound possesses a unique extractability under different conditions of supercritical fluid related to factors such as extraction temperature, pressure, and time.…”
Section: Introductionmentioning
confidence: 99%
“…SFE of lipids has received attention as an alternative to organic solvent extraction and has been shown to be an ideal method for extracting certain lipids (Garcia et al, 1996). Garcia et al (1996) reported that most studies of the use of SFE in lipid extraction have focused on the yield of extractable material.…”
Section: Introductionmentioning
confidence: 99%
“…For extraction of RBO, attempts using supercritical fluid extractions with CO 2 [2,[13][14][15] and methanol/CO 2 [16] were reported by several groups. A maximum RBO yield of 20.5%, which represents over 99% of lipid recovery, was reportedly obtained with a conventional approach using hexane, while the yield with supercritical CO 2 extraction ranged between 19.2 and 20.4% [2,15].…”
Section: Introductionmentioning
confidence: 99%